The Essential Guide to Game Audio : The Theory and Practice of Sound for Games - Horowitz, Steve, ....-; Looney, Scott, ....- (New York : Focal Press, 2014)
The Essential Guide to Game Audio: The Theory and Practice of Sound for Games is a first of its kind textbook and must-have reference guide for everything you ever wanted to know about sound for games. This book provides a basic overview of game audio, how it has developed over time, and how you can make a career in this industry. Each chapter gives you the background and context you will need to understand the unique workflow associated with interactive media. The practical, easy to understand interactive examples provide hands-on experience applying the concepts in real world situations.
Keywords: Game Audio; Game Design; Video Games